REVOLUSI MENTAL DALAM MEMBENTUK KARAKTER MELALUI NILAI-NILAI PENDIDIKAN MULTIKULTURAL - Firdha Aprillia Lilura (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
The mental revolution changes the perspective, thoughts, attitudes and behaviors that are oriented towards progress and modernity, so that it becomes a great nation and is able to compete with other nations in the world. Mental Revolution becomes a word that can make us realize that there are important things that need to be improved in the mentality of the people of this nation. We learn from several other countries in achieving economic progress but still maintain local local wisdom. Hard work, social spirit, nationalism, love of the country and love of domestic products are positive things that are important for us to realize. Building a good mentality can be realized with multicultural values education, which covers things such as, culture, ethnicity, gender, social and religion that tend to be more comprehensive for the typical Indonesian people in this study to present ways that can revolutionize the nation’s mental Indonesia has become more broad-minded and has strong thinking, with diverse Multicultural values in Indonesia. This study uses descriptive method of literature review. Seeing the situation in this age from research conducted by changing the perspective, attitude and behavior, mental, etc., which is oriented towards the progress of the nation is better expected from multicultural values.